Assessment of Coastal Vulnerability to Support Mangrove Restoration in the Northern Coast of Indramayu Regency - Nabila Fathimatuzzahra; Yudi Setiawan; Syamsul Bahri Agus (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2026)
Indramayu Regency, a low-lying coastal area in West Java, has experienced substantial mangrove deforestation. Climate change, worsened by global warming, which causes rising sea levels, has made coastal ecosystems vulnerable. Mangroves play an important role in preventing ecological imbalance in coastal ecosystems and play a role in securing local livelihoods. Considering the dense population on the Indramayu coast, it is imperative to conduct vulnerability mapping as a decision support for policymakers to implement sustainable coastal management in Indramayu. This study aimed to develop a Coastal Vulnerability Index (CVI) for the Indramayu coastal ecosystem using a geospatial analysis of multiple parameters: geomorphology, shoreline change rates, sea level rise, wave height, coastal slope, and tidal range. The methodology employed a grid-based approach (4×4 km²) along the coastline to identify priority zones for restoring mangroves. This study also included the Mangrove Vulnerability Index (MVI) assessment and combined it with relevant policy documents to provide recommendations for mangrove restoration efforts. The results indicate severe coastal vulnerability, with 37.14% of the area classified as highly vulnerable. In contrast, mangrove ecosystems showed greater resilience, with 77.14% of the grids categorized as having low vulnerability. These findings provide science-based recommendations for policymakers to prioritize resource allocation in mangrove restoration programs.